Semi-Active Damping of Vibrations. Prestress Accumulation-Release Strategy Development - A. Mroz; A. Orlowska; J. Holnicki-Szulc (Shock and Vibration)
New method for semi-active control of vibrating structures is introduced. So-called Prestress Accumulation-Release (PAR) strategy aims at releasing of the strain energy accumulated in the structure during its deformation process. The strain energy is converted into kinetic energy of higher modes of vibration which is suppressed with structural damping or by means of a damping device. The adaptation process essentially affects the first mode vibrations by introducing an elastic force that opposes the movement. Numerical simulations as well as experimental results prove that the strategy can be very effective in mitigating of the fundamental mode of a free – vibrating structure. In a numerical example 95% of the vibration amplitude was mitigated after two cycles. An experimental demonstrator shows 85% reduction of the amplitude in a cantilever free- vibrations. In much more complex practical problems smaller portion of total energy can be released from the system in each cycle, nevertheless the strategy could be applied to mitigate the vibrations of, for example, pipeline systems or pedestrian walkways.